2014
DOI: 10.12809/hkmj134082
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal deep brain stimulation: an effective treatment in Chinese patients with tardive dystonia

Abstract: A B S T R A C TTardive dystonia is an iatrogenic complication of dopamine receptor antagonist medication such as first-generation antipsychotics. It occurs in up to 2% of patients and only 10% recover after stopping medication. Deep brain stimulation for primary dystonia has proven to be effective and its application for secondary dystonias is gaining acceptance. We report our experience in treating three ethnic Chinese schizophrenia patients with severe medically refractory tardive dystonia by globus pallidus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A study from Japan by Koyama H et al showed a significant improvement in mean Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) scores at 1 month postoperatively of 75% with long-term improvement in BFMDRS scores of 78.0% ( 145 ). Another case report showed that pallidal DBS was an effective treatment for Chinese patients with tardive dystonia with an improvement in BFMDRS scores of 77% and in Global Dystonia Rating Scale scores of 66% ( 146 ). Although the effectiveness of DBS in TD and tardive dystonia is promising, further studies with DBS in other tardive syndromes are needed in Asian patients.…”
Section: Strategies For Minimizing and Managing Tdmentioning
confidence: 99%
“…A study from Japan by Koyama H et al showed a significant improvement in mean Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) scores at 1 month postoperatively of 75% with long-term improvement in BFMDRS scores of 78.0% ( 145 ). Another case report showed that pallidal DBS was an effective treatment for Chinese patients with tardive dystonia with an improvement in BFMDRS scores of 77% and in Global Dystonia Rating Scale scores of 66% ( 146 ). Although the effectiveness of DBS in TD and tardive dystonia is promising, further studies with DBS in other tardive syndromes are needed in Asian patients.…”
Section: Strategies For Minimizing and Managing Tdmentioning
confidence: 99%
“…small groups of 2-4 people [44,65,67,69,77,86,87] or slightly larger groups [40,43,74,79,81,88,89] when 19 patients were the largest cohort [37].…”
Section: Internal Globus Pallidus (Gpi)mentioning
confidence: 99%
“…T. Tsuboi, et al Parkinsonism and Related Disorders 70 (2020) [82][83][84][85][86][87][88][89][90][91][92][93] Some other studies reported the long-term efficacy of GPi or STN DBS on tardive dystonia with variable assessment scales as summarized in Table 3 [60][61][62][63]. One study found that, after GPi DBS, HRQoL domains according to SF-36 (role physical, and social functioning, and PCS) significantly improved at a mean follow-up of 3.4 years [62].…”
Section: Tardive Dystoniamentioning
confidence: 99%